Redefining urban assessment criteria towards sufficient future cities / Rostam Yaman ... [et al.] - Yaman, Rostam; Thadaniti, Suwattana; Adnan, Hamimah; Ahmad, Noraini (Faculty of Architecture, Planning and Surveying, 2016)
Urbanized areas are typically the most significant sources of environmental degradation, thus, an urban assessment criteria tools aiming at sufficient/self-sustain of the natural environment needs to be firmly embedded in benchmarking planning and design framework. The theoretical model of Sufficient Future Cities (SFC) criteria framework of both qualitative and quantitative evaluation and benchmarking will be develop toward urban sufficient/self-sustain. The SFC sets out a vision for sustainability within the built environment and provides guidance to deliver sustainable townships through six primary dimensions of environmental design and planning. The SFC framework runs on four primary methodology process and sequence in order to optimize urban sufficiency and self-sustaining criteria. Even though the SFC framework is one of the many methods in which to evaluate and benchmark tools to be developed for a comprehensive sustainable township, the principal argument is that comprehensive sufficient/self-sustain is certainly possible if it is properly conceived and implemented through responsible urban design and planning developments.